La Imprenta de Martín Biedma (1872-1910) - Cabo, Josefina (2014)
Establecida en 1872, la imprenta de Martín Biedma se convirtió pronto en uno de los talleres gráficos porteños más importantes entre el último cuarto del siglo XIX y el Centenario, y logró reputación por la calidad de sus impresiones. Su crecimiento se dio en un momento de auge de la industria del libro en Buenos Aires, en que se implementaron cambios que modernizaron el oficio del tipógrafo y los talleres de impresión. La primera edición de Potpourri (1882), de Eugenio Cambaceres, es evaluada en relación con el desarrollo y las características de la imprenta y el período
Established in 1872, the printing house of Martín Biedma soon became one of the most important publishers in Buenos Aires between the last quarter of the 19th century and the Centennial, and earned a reputation for the quality of its products. Its growth took place in a flourishing period of book industry in Buenos Aires, during which various improvements were made to modernize the profession of typographer and the printing establishments. The first edition of Potpourri (1882), by Eugenio Cambaceres, is considered in relation with the development and characteristics of this particular printing house and the epoch in question
Keywords: Imprenta; Martín Biedma; Potpourri; Siglo XIX; Printing; Martín Biedma; Potpourri; 19th century